Dispositivo portátil utilizado para avaliação da hipertonia da articulação do tornozelo em indivíduos com paralisia cerebral - Fonseca, Letícia Alves (2011)
The aim of the present study was to evaluate the applicability of a portable device for measuring hypertonia of the ankle joint in subjects with spastic cerebral palsy. An uncontrolled, observational, cross-sectional study was carried out with convenience sample. For such, 42 individuals were initially screened at the UNINOVE clinic school (Brazil). After application of the inclusion and exclusion criteria, 28 individual were selected and classified according to GMFCS levels I,II AND III; 14 subjects (8.5 ± 0.7 years) were included in the first study and 17 subjects (9.6 ± 2.3 years) were included in the second study. Functionality was evaluated using the Berg balance scale for the assessment of functional balance and GMFM-66 to measure gross motor function. Functional balance was positively correlated with the gross motor function on the activities of crawling, kneeling, standing, walking, running and jumping, as proposed by the GMFM-66 (p < 0.01). Hypertonia was then assessed the modified Ashworth scale(MAS) and a portable device developed by the Polytechnic Institute of Milan. The MAS and portable device exhibited a highly negative correlation, a greater degree of hypertonia determined by MAS which is in agreement with findings reported in the literature. The MAS and portable device exhibited the same behavior in the evaluation of ankle hypertonia in individuals with cerebral palsy, suggesting that portable device may be used as additional resource for the evaluation of these individuals in clinical practice.